Contrasting sources and «game of mirrors». A methodological approach to the Spanish Civil War experience studies - Raya Crespi, Daniel (Huarte de San Juan. Geografía e Historia, 2023)
The main objectives of this article are to present the trajectory of the War Experience as a historiographical issue, focusing mostly on the trajectory it has had in the Spanish academy, and to problematize this line of study through the critical analysis of its primary sources. For that purpose, three different types of sources suitable for the investigation of the republican combatants’ war experience will be proposed (ego-documents, front publications and military documentation). Their interpretative potential will be assessed, as well as the consequent pitfalls of their nature. Based on these approaches, the importance of properly using a source will be illustrated to get the most out of it interpretatively, as well as how vital it is to find other sources with which they can be contrasted.